1999
DOI: 10.1034/j.1399-3089.1999.00015.x
|View full text |Cite
|
Sign up to set email alerts
|

IgY antiporcine endothelial cell antibodies effectively block human antiporcine xenoantibody binding

Abstract: Avian IgY antibodies are structurally different from mammalian IgGs and do not fix mammalian complement components or bind human Fc receptors. As these antibody-mediated interactions are believed to play significant roles in both hyperacute rejection (HAR) and acute vascular xenograft rejection (AVXR), IgY antibodies to xenoantigen target epitopes may inhibit these rejection processes. In this report, we show that chicken IgY antibodies to alpha-Gal antigen epitopes and to other porcine aortic endothelial cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 49 publications
0
19
0
1
Order By: Relevance
“…Complete eradication of exogenous viral infection and removal of endogenous retrovirus, however, has been reported (26). …”
Section: Discussionmentioning
confidence: 99%
“…Complete eradication of exogenous viral infection and removal of endogenous retrovirus, however, has been reported (26). …”
Section: Discussionmentioning
confidence: 99%
“…Immunological staining has shown that in pig tissue there are several antigens with different Galα1‐terminated epitopes 26 , 27 ). Xenoreactive antibodies may thus exhibit broad specificities by reacting with Galα1‐3Gal determinants being either terminally located or present as core structures 28 .…”
Section: Discussionmentioning
confidence: 99%
“…One possible way is to block the epitope with anti‐αGal IgY, made in the chicken, because IgY does not activate mammalian complement or bind to mammalian Fc receptors. Previously we have shown that IgY anti‐αGal pretreatment of porcine endothelial cells blocks human XNA binding, complement activation and antibody‐dependent cell‐mediated cellular cytotoxicity (ADCC)‐type effector functions 12 …”
Section: Discussionmentioning
confidence: 99%
“…Anti‐αGal IgY was prepared by immunizing chickens with αGal epitope conjugated to ovalbumin or keyhole limpet haemocyanin, isolating the IgY fraction from egg yolks, and affinity purifying the anti‐αGal fraction using Synsorb‐90 beads as previously described 12 . The portion of IgY which did not bind to the αGal epitope on the Synsorb‐90 matrix was termed the IgY flow‐through (FT‐IgY).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation